SEKOLAH RUJUKAN (Studi Evaluatif di SMKN 1 Kota Bengkulu) - yoga firnanda; Manap Somantri (UNIVERSITAS BENGKULU, 2020)
Abstract: This study aims to describe the basis and process of establishing Bengkulu City Vocational High School 1 as a reference school. This study uses an evaluative approach, Setting Research conducted at the Vocational High School I Bengkulu City. The subjects of this study were the Principal, Education Quality Assurance Team of the Vocational High School 1 Vocational School referral city Bengkulu City. Data collection techniques using interviews, observation, and study documentation. The results of the study are as follows: SMK 1 Bengkulu City became a reference school since 2014 with the fulfillment of quality standards and national education standards, after going through a process of verification, selection, and presentation at the central level. Bengkulu City Vocational School 1 as a reference school has carried out its role as a reference school by providing guidance to alliance schools, so that the referral school program can improve management of quality management, so that the quality of education, education, and the capacity of teachers and principals, especially in Vocational Middle School 1Bengkulu city as reference schools and alliance schools under the guidance of Vocational Middle School 1 Bengkulu City. Keywords: Reference Schools, Quality Management, National Education Standards.